(untitled) - Strange, Susan (London, 1988)
Professor Strange is known for her unorthodox views on the international political economy. Here, she provides the student and scholar with a new model synthesizing politics and economics by means of a four-faceted structural analysis of the effects of any kind of political authority (including states) on markets and, conversely, of market forces on states. This framework of analysis should serve as an introductory text
Keywords: International economic relations